2001
DOI: 10.1007/s001980170155
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Lifestyle Factors on Stress Fractures in Female Army Recruits

Abstract: Estimates are that stress fractures during basic training (BT) occur in as many as 14% of US female military recruits. Injuries of this type lead to morbidity ranging from minor pain to serious lifetime disability. Since women are assuming an increasing role in the military, this high risk of stress fracture is of concern. The purpose of this prospective study was to determine factors that predict stress fracture during BT in US Army female recruits. The analysis was part of an investigation using quantitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
126
1
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 180 publications
(139 citation statements)
references
References 36 publications
8
126
1
3
Order By: Relevance
“…This can lead to bone loss and subsequent micro-damage that can result in localised bone weakening, prompting stress fracture development (2). Stress fracture period prevalence in elite athletes and military recruits ranges from 14 to 21% (3,4), and most commonly manifests in the lower limbs (5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can lead to bone loss and subsequent micro-damage that can result in localised bone weakening, prompting stress fracture development (2). Stress fracture period prevalence in elite athletes and military recruits ranges from 14 to 21% (3,4), and most commonly manifests in the lower limbs (5).…”
Section: Introductionmentioning
confidence: 99%
“…Susceptibility may also have genetic origins, supported by reports of monozygotic twins developing similar stress fracture injuries (8), multiple stress fractures occurring in the same individual (9), stress fractures occurring in some individuals but not in others undertaking identical training protocols (3,4) and a family history of stress fracture injury acting as a risk factor (10).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Lappe et al analysed 3,758 female recruits and found that after eight weeks of basic training stress fractures were more likely to be reported by recruits with a current or past history of smoking or regular consumption of alcohol [5]. We also analysed lifestyle risk factors and found nicotine abuse in 46.7 % of male patients within the study group and thus significantly more often compared to female patients.…”
Section: Discussionmentioning
confidence: 87%
“…Stress fractures have been reported to be a common problem in young and active people such as athletes and military recruits [1][2][3][4][5]. Based on their aetiology, stress fractures can be subdivided into either fatigue-or insufficiency-related fractures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation